The Role Of Trust As A Mediator Between Extraversion And Knowledge Sharing Of High School Employees - Evada Rustina; Asri Laksmi Riana; Nur Wening (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study is to test the effect of Extraversion (EXT), and Trust (TRU) on Knowledge Sharing (KSH), and to examine the role of TRU in mediating EXT and KSH. The study was conducted on 105 employees of the High School. Data was collected using a questionnaire with a Likert scale and analyzed with SEM PLS. The results of the study proved that EXT and TRU positively affect KSH. TRU has also been shown to play a role in mediating between EXT and KSH. The findings from this study suggest that schools have the opportunity to enhance knowledge-sharing behavior among employees. This research adds valuable insights to the existing academic literature by exploring the connection between extraverted personality, trust, and knowledge-sharing behavior. Fostering a culture of trust among school staff is crucial to promoting knowledge sharing.